Limited population and community effects of hatching asynchrony in a pond‐breeding salamander. Issue 2 (21st February 2023) - Anderson, Thomas L.; Burkhart, Jacob J.; Cianci‐Gaskill, Jacob A.; Davenport, Jon M.
Abstract: Understanding attributes of phenology beyond the mean date of a life history event, such as variability among individuals within a population, is critical to predict how climate‐induced phenological shifts may alter population dynamics. Identifying how phenological variability impacts organisms is especially needed to better understand how phenological shifts affect trophic dynamics (e.g., shifts in variability of top predators affecting primary production). To better understand the effects of phenological variability on both populations and communities, we examined how variation in egg hatching synchrony of predatory marbled salamanders ( Ambystoma opacum ) impacted intraspecific interactions at the larval stage, ultimately affecting demographic traits and survival through metamorphosis. We also examined how hatching synchrony affected overall trophic dynamics (e.g., primary consumers and producers) in pond food webs. We experimentally manipulated the degree of hatching synchrony of embryonic A. opacum and subsequently reared larvae in outdoor mesocosms. We monitored demographic traits such as larval growth, size at and time to metamorphosis, and survival. To assess trophic dynamics, we monitored zooplankton abundance and phytoplankton biomass during the experiment. Larvae exhibited greater variability in body size in medium and low hatching synchrony treatments compared to high synchrony treatments. Larval body size variation diminished over time to ultimately result in no differences in most life history traits at metamorphosis or survival among hatching synchrony treatments. We also found no differences among treatments in zooplankton abundance or phytoplankton biomass, likely because of minimal variation in A. opacum survival among treatments that would induce top‐down changes. Overall, we found that phenological variation may be context dependent in its influence on demography and overall community structure. Because of concerns for how phenological shifts will affect species interactions, greater scrutiny into conditions that would promote changes in population and community dynamics is needed.